แนวทางการจัดการความรู้ด้านงานพัสดุของสำนักงานพัฒนาที่ดินเขต 6 - พัชราภรณ์ อุตตมา (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The objectives of this research were to investigate contexts knowledge management and to develop knowledge management guidelines for Procurement Division of Land Development Regional Office 6. The qualitative research was implemented in this research. The population are 2 groups which are the procurement supervisor and parcel worker. There are 8 interviewees. The research tool was Semi- Structured interview and analytical tools in data analysis is content analysis. The research results were found that Problems related to knowledge management is knowledge sharing that there is an exchange and sharing of knowledge specific to the problem area there is not dissemination to share knowledge from attending meetings, trainings, seminars to others. The result of Knowledge management process found; knowledge creation and acquisition from the seminar and attending meetings inquiries from the responsible person to find solutions and knowledge transfer there are studies to find information from the internet databases and resources. There are 3 knowledge organization collecting: 1) knowledge of procurement 2) knowledge of parcel control and 3) knowledge of parcel inspection. The supporting factors for knowledge management of procurement are (1) infrastructure, technology and process factors (2) personal factors in leadership (3) factors of working skills especially knowledge skills and competence and (4) organizational factors. For the guidelines to provide the development of knowledge management for Procurement Division, there were 3 issues as follows: 1) the operator of the supplies and personnel in the organization. There is still a lack of knowledge and understanding of knowledge management, so the policy on supplies should be clearly formulated and the goals are announced and guidelines for knowledge management of supplies for staff and personnel by establishing a knowledge management team responsible for the knowledge management of supplies to come to work in the knowledge management field of supplies promote the participation and communication of parcel workers regularly through multiple channels such as leveraging social media such as Facebook Line by creating a Communities of Practice: CoP group, as well as being responsible for organizing activities various that encourages the exchange of knowledge on supplies. 2) Knowledge management process, including knowledge sharing, knowledge creation and acquisition, knowledge storage and knowledge transfer should use information technology to support the process, such as using Zoom or Microsoft Teams in a meeting, to consulting on operational problems follow-up of knowledge management including online training in a mentoring system. 3) should have a Knowledge Base to storing and disseminating knowledge by Google Drive and Facebook group. The retrieval rights are set for parcel workers and the general public and 4) should monitor the application of knowledge management this can be done by surveying the statistics on the number of queries related to the supply chain, if the statistics are reduced and if the organization can reduce operating procedures it brings convenience, speed, cost reduction and resource consumption. It is considered to achieve the goal of knowledge management in the organization as well as being able to explore satisfaction evaluate the effectiveness of knowledge management in the organization. Performance tracking or evaluation through Google Forms that can be connected to Google Drive to store results and can be used immediately.